Use of nicotinamide in dermatology. (4th January 2017) - Forbat, E.; Al‐Niaimi, F.; Ali, F. R.
Summary: Nicotinamide (niacinamide) is the water‐soluble, amide form of vitamin B3. We review the evidence underlying the use of nicotinamide for various dermatological indications, including nonmelanoma cancer prophylaxis, blistering disorders, acne vulgaris and cosmetic indications, and speculate upon its future role in dermatological practice. Abstract : Clickhere for the corresponding questions to this CME article.